حقوق الموظف العام وحمايتها في القانون الجزائري - دبة عبد الغاني أ - حرايز محمود (جامعة المسيلة, 2024)
من خالل دراستنا لموضوع حقوق الموظف العمومي وحمايتها في القانون الج ازئري، تبين لنا أن الموظف العام بمثابة األداة البشرية التي تعتمد عليها اإلدارة من أجل تحقيق الغرض الذي أنشئت له، لذا جعلت له أغلب التشريعات والتنظيمات حقوقا أساسية من جهة تمكنه من أداء مهامه ومن جهة أخرى تحصنه وتحميه من أي تعسف قد يمس بحقوقه. يتمتع الموظف العام بحقوق أصلية يكتسبها بمجرد تعاقده مع اإلدارة وتبقى تابعة له حتى بعد إنهاء هذا التعاقد، والزيادة في الحقوق الممنوحة للموظفين وتنوعها يتماشى والتطور الكبير الذي يشهده نشاط اإلدارة العامة وتنوعه. الكلمات المفتاحية: الموظف العمومي، الحقوق المادية، حقوق المعنوية، الحماية المادية، الحماية المعنوية Abstract : Through our study of the issue of public employee rights and their protection in Algerian law, we found that the public employee is the human tool that the administration relies on in order to achieve the purpose for which it was created. Therefore, most legislation and regulations have granted him basic rights, on the one hand, enabling him to perform his duties, and on the other hand, protecting him. It protects him from any abuse that may affect his rights. The public employee enjoys original rights that he acquires as soon as he contracts with the administration and that remain subordinate to him even after the termination of this contract. The increase in the rights granted to employees and their diversity is in line with the great development witnessed in the activity of public administration and its diversity. Keywords: public employee, material rights, moral rights, material protection,
Keywords: الكلمات المفتاحية: الموظف العمومي، الحقوق المادية، حقوق المعنوية، الحماية المادية، الحماية المعنوية